DoS Flooding Attacks against SIP based VoIP Systems- a Survey - Kaur, Mandeep; Kumar, Santosh; Sharma, Swati (International Journal of Computer Sciences and Engineering, 2014)
The success of the Internet has brought significant changes to the telecommunication industry. One of the remarkable outcomes of this evolution is Voice over IP (VoIP), which enables real time voice communications over packet switched networks for a lower cost than traditional public switched telephone networks (PSTN).VoIP networks are more vulnerable to security threats as compared to traditional PSTN due to their open environment such as the Internet and use of open standard like Session Initiation Protocol (SIP), launching an attack on a telephony server is much simpler. Availability is one of the major issues of computer security, along with confidentiality and integrity. Denial of service (DoS) is a threat that potentially violates the availability of a resource in a system. In this survey, we are discussing the DoS flooding attack on SIP server. Firstly, we present a brief overview about the SIP protocol. Then, we discuss security attacks related to SIP protocol. After that, we talk about the detection techniques of SIP flooding attack and various exploited resources due to attack.